1990
DOI: 10.1111/j.1525-1446.1990.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Hispanics: At Risk for Adolescent Pregnancy?

Abstract: Data from the Hispanic Health and Nutrition Examination Survey, 1982-1984, were analyzed to describe pregnancy, miscarriage, and age-specific birth rates as well as oral contraceptive use among Mexican-American, Puerto Rican, and Cuban-American females age 12 to 19 years. The Cuban-American sample (n = 85) had the lowest pregnancy (99) and fertility (37) rates, with 6.5% ever having used oral contraceptives. In the Mexican-American (n = 638) and Puerto Rican women (n = 300) the pregnancy and fertility rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…They found that Hispanic studentswere more likely to have an older boyfriend/girlfriend, and that having an older boyfriend or girlfriend was associated with early sexual onset. PIetsch (1990) concluded, based on data from the Hispanic Health and Nutrition Examination Survey, that Mexican-Americans and Puerto Ricans are at higher risk for adolescent pregnancy.…”
Section: Sexual Risk Behavior Among Hispanic Adolescentsmentioning
confidence: 97%
“…They found that Hispanic studentswere more likely to have an older boyfriend/girlfriend, and that having an older boyfriend or girlfriend was associated with early sexual onset. PIetsch (1990) concluded, based on data from the Hispanic Health and Nutrition Examination Survey, that Mexican-Americans and Puerto Ricans are at higher risk for adolescent pregnancy.…”
Section: Sexual Risk Behavior Among Hispanic Adolescentsmentioning
confidence: 97%
“…This conjecture is plausible but difficult to test because it requires accurate records on all cases of fetal loss as well as data on the risk profiles for all women who become pregnant, not just of those who give birth. Preliminary findings from the Hispanic Health and Nutrition Examination Survey (HHANES) and NSFG undermine the hypothesis that selection due to fetal loss could explain the paradox because they reveal that rates of fetal deaths are lower among the three largest Hispanic groups, and are lowest for Mexican Americans 41,45. Other research, however, suggests that it is perhaps premature to rule out the contribution of this mechanism because rates of fetal deaths by parity display larger ethnic variability than previously thought, and appear to be unfavorable for Mexican Americans for pregnancies of third or higher order 22.…”
Section: The Matter Of Selectionmentioning
confidence: 99%
“…Birthrate for Hispanic females aged 1517 is 65/100,000 compared to 23 births/100,000 for white females (Alan Guthnacher Institute, 1994). Hispanic adolescents are at high risk for pregnancy (Pletsch, 1990) and sexually transmitted diseases (STDs), including HIV and AIDS (Ellerbrock, Bush, Chamberland, & Oxtoby, 1991;Rolfs & Nakashima, 1990). As a whole, Hispanics have the second highest rates of gonorrhea and syphilis and they account for 15% of the nation's AIJ3 cases in youth ages 13-19 years (National Coalition of Hispanic Health and Human Services Organizations [COSSMHOI, 1995).…”
Section: Mexican-american Adolescentsmentioning
confidence: 99%